Pembuatan Bulu Mata Fantasi dari Serat Daun Lidah Mertua untuk Peluang Berwirausaha - Putri Yuliana Angelika; Agus Susanti; Sofia Daniat (Akademi Kesejahteraan Sosial Ibu Kartini Semarang, 2025)
Fantasy eyelashes are eyelashes that are used to add an accent of beauty to fantasy eye makeup. Currently, fantasy eyelashes are rarely sold on the market, and most of them are relatively expensive with simple designs. The scarcity of fantasy eyelashes at relatively high prices has led the author to innovate by utilizing mother-in-law's tongue leaf fibers as the basic material for making fantasy eyelashes. The research aims to simplify the search for fantasy eyelashes needed by the public at an affordable price while using natural materials that minimize the risk of irritation, thereby presenting an entrepreneurial opportunity. The natural material used is the mother-in-law's tongue plant. This plant is an environmentally friendly ornamental plant that is easily found in the author's surroundings, highly beneficial for health as it filters toxins and air pollution, and has high economic value. This research employs observation, literature review, experimentation, documentation, and questionnaires. The author uses descriptive qualitative analysis, presenting research results in narrative form using words and sentences. The author offers a price of Rp. 35,000 per pair, which is competitive with market prices for fantasy eyelashes. Product validation was conducted through sensory testing with three expert validators, covering aspects such as texture, shape, neatness, and a rating of 15 in the “very suitable” category. The level of preference was assessed through a preference test with 60 respondents, covering statements 1 to 8, with results ranging from 241 to 300 indicating “very liked.” This study concludes that fantasy eyelashes made from mother-in-law's tongue leaves can compete and are favored by makeup artists and practitioners.